Analisis Yuridis Sengketa Antara Malaysia dan Indonesia Terkait Klaim Atas Pulau Sipadan dan Ligitan - Lesmana, Annafi Tri; Jamba, Padrisan (Universitas Pahlawan Tuanku Tambusai, 2025)
Objective from study This done For know Dispute region between Malaysia and Indonesia related claim on island Sipadan And Ligation is complex issue in second bilateral relationship country. through method study normative Background behind dispute This started from claim historical And difference interpretation to agreements that have there. In review to agreements that have there, like Territorial Boundary Agreement 1969 and The 1971 Five Nations Declaration, view that agreement the influence claim sovereignty from second country on island Sipadan And Ligation. However, differences interpretation And interpretation to agreement the Still become source conflict between Malaysia and Indonesia related dispute region this. In writing This that writer give conclusion that negotiation Based on Law International : Second country must prioritize negotiation based on law international And its principles. Agreement inherited borders from period colonial English And agreement border other must become footing For look for fair solution And in accordance with law international.